Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

20e anniversaire! Héritages féministes : tensions et parallèles - Institut de recherches et d'études féministes (FéminÉtudes, 2015)
Cette publication célèbre les 20 ans de FéminÉtudes et revient sur les moments forts de la revue. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-20-no-1-2015-20e-anniversaire-heritages-feministes-tensions-et-paralleles/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; féminétudes; genre; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; militance; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; écriture des femmes*

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

La violence intersectionnelle dans la pensée féministe autochtone contemporaine - Perreault, Julie (Recherches féministes, 2015)
En parallèle avec les luttes des femmes sur le terrain, un courant théorique du féminisme autochtone se développe depuis la fin des années 90. Celui-ci revisite le narratif de la colonisation et la théorie postcoloniale en y intégrant l’analyse genre/« race ». L’auteure tente d’inscrire cette production intellectuelle au sein du paradigme intersectionnel universitaire et de la rendre accessible à un public francophone qui la connaît souvent moins bien. En replaçant la violence sexuelle et le patriarcat d’État au centre du débat, les féminismes autochtones arrivent à percevoir une dimension politique souvent laissée de côté par les analyses intersectionnelles.
http://www.recherchesfeministes.ulaval.ca
Keywords: approches et analyses; cours; discipline; fem1000; femmes* autochtones; féminisme décolonial; genre; identités LGBTQIA2+; intersectionnalité; pol4105; premier cycle; ressource en ligne; science politique; science politique et droit; sex2283; thématiques; violences